Effect of steel reinforcement in flexural strengthening of RC slabs using prestressed NSM CFRP laminates - Hosseini, Mhoammadreza Mostakhdemin (2018)
The influence of the percentage of the longitudinal tensile reinforcement on the effectiveness of the NSM (near surface mounted) technique with prestressed CFRP (carbon fiber reinforced polymer) laminates for the flexural strengthening of RC (reinforced concrete) slabs was assessed experimentally. Four RC slabs were tested, a reference slab (without CFRP), and three slabs flexurally strengthened using NSM CFRP laminates with different prestress levels, which was considered a percentage of their ultimate tensile strength namely: 0%, 20% and 40%. The tested slabs had a percentage of longitudinal tensile steel bars of about 0.62% (ρsl =0.62%), while the CFRP strengthening percentage was approximately 0.085%. The results obtained indicated that prestressing CFRP laminates with the NSM technique is a suitable strategy to increase the flexural capacity of RC slabs, not only in ultimate but also in serviceability limit states. By applying NSM CFRP laminates prestressed at 20%, the service and maximum loads increased by 42% and 59%, respectively, compared to the reference slab. The values of service and maximum loads increased by 79% and 64%, respectively when applying laminates prestressed at 40%. Considering available experimental results obtained with the same test setup, but using RC slabs with lower percentage of the longitudinal tensile reinforcement (ρsl =0.35%), it can be concluded that the increase of the percentage of the longitudinal tensile reinforcement has a detrimental effect on the effectiveness of NSM technique with prestressed CFRP laminates in terms of the increase of service and ultimate loads.